Die beste Bildungspolitik ist ein gute Ordnungspolitik: Eine Erwiderung - Dominik Enste; Jochen Wicher (Wirtschaftsdienst, 2013)
In der Juniausgabe 2012 veröffentlichte der Wirtschaftsdienst einen Aufsatz mit dem Titel 'Regulierung, Bildung und Wohlstand - der IW-Regulierungsindex'. Enrico Schöbel und Lars Petersen setzen sich damit kritisch auseinander und Dominik H. Enste und Jochen Wicher erläutern ihren Standpunkt in einer Erwiderung. – – Enste and Wicher suggest that political regulation is always wealth-reducing. However, their analysis neglects various relevant determinants of the wealth indicator. Economic wealth cannot be estimated from the quantity of regulation, as quality and other aspects matter. Hence, political acumen is required. Enste and Wicher reply to criticism of the regulation index and the analysis of the impact of regulation on education. They argue that they neither ignore the positive effects of regulation (taken into account with the data on good governance indicators) nor demand a zero regulation policy. Instead, the main goal of the analysis is to provide an international comparison for 'better regulation'.
Keywords: H11; I25; I28; K23; L51; O43; 330; Ordnungspolitik; Bildungsreform; Wohlfahrtsanalyse; Deutschland